Peran Conservation International (CI) Terhadap Konservasi Perairan di Bali (Studi Kasus: Desa Tulamben, Bali) - Timothy Fabian Theodurrus; Aswin Baharuddin; Bama Andika Putra (Department of International Relations, Hasanuddin University, 2021)
This study aims to determine Conservation International's strategy for Aquatic Conservation in Tulamben, Bali and the impact resulting from Conservation International on Aquatic Conservation in Tulamben, Bali. The research method used in the preparation of this thesis is descriptive method, with data collection techniques in the form of reviewing books, journals, articles, official internet sites, as well as reports or documents related to this research. The results of this study found two things. First, Conservation International's strategy for Marine Conservation in Tulamben, Bali, which is to play a role in managing policies and regulations with the Tulamben Village government and participating with the community in the context of integrating the Marine Protected Area (KKP) program. Second, the impact of Conservation International on Marine Conservation in Tulamben, Bali is divided into three dimensions, namely social, environmental and economic. The social impact is the active role of the community in the Conservation International program. Environmentally, there is growth of fish varieties in the conservation area of ​​Tulamben Village. And the economic impact is the increase in hotel accommodation in Tulamben and local workers. Penelitian ini bertujuan untuk mengetahui strategi Conservation International terhadap Konservasi Perairan di Tulamben, Bali dan dampak yang dihasilkan dari Conservation International terhadap Konservasi Perairan di Tulamben, Bali. Metode penelitian yang digunakan dalam penyusunan skripsi ini adalah metode deskriptif, dengan teknik pengumpulan data berupa telaah buku, jurnal, artikel, situs internet resmi, serta laporan atau dokumen yang berkaitan dengan penelitian ini. Hasil penelitian ini menemukan dua hal. Pertama, strategi Conservation International terhadap Konservasi Perairan di Tulamben, Bali yaitu berperan dalam pengelolaan kebijakan dan regulasi bersama pemerintah Desa Tulamben serta partisipasi bersama masyarakat dalam konteks integrasi program Kawasan Konservasi Perairan (KKP). Kedua, dampak Conservation International terhadap Konservasi Perairan di Tulamben,Bali terbagi atas tiga dimensi, yaitu sosial, lingkungan, dan ekonomi. Adapun dampaknya secara sosial yaitu peran aktif masyarakat dalam program Conservation International. Secara lingkungan, adanya pertumbuhan varietas ikan di areal kawasan konservasi Desa Tulamben. Dan dampaknya secara ekonomi yaitu meningkatnya akomodasi perhotelan di Tulamben serta tenaga kerja lokal.